Efficiency of neuromuscular electrical stimulation: A comparison of elicited force and subject tolerance using three electrical waveforms. (3rd July 2018) - Bellew, James W.; Allen, Molly; Biefnes, Austin; Grantham, Sara; Miglin, James; Swartzell, Dylan
ABSTRACT: Objective : Efficacy of neuromuscular electrical stimulation (NMES) is limited by the discomfort of electrically elicited contractions. Most studies of tolerance to NMES have examined stimulation to maximal tolerance. NMES efficiency is the amount of elicited force at a specific level of tolerance. This study is the first to describe and examine such. Design : A repeated measures design was used. Electrically elicited force (EEF) was measured using three waveforms: burst-modulated alternating current (BMAC), pulsed current (PC), and burst-modulated pulsed current (BMPC). EEF at a tolerance rating of 5/10 on a visual analog scale (VAS) was recorded. The dependent variables were EEF up to 5/10 VAS, current amplitude at 5/10, and percent maximal isometric force at 5/10. Results : EEF and percent maximal voluntary isometric force were significantly greater with BMPC versus BMAC ( p  = 0.001 and 0.004). No differences were noted between PC and BMAC or BMPC and PC. Amplitude was significantly greater with BMAC compared to BMPC and PC ( p  = 0.003 and 0.015). No difference in amplitude was noted between PC and BMPC. Conclusion : For the same level of discomfort, BMPC yielded one-third greater muscle force than BMAC and at a lesser current amplitude. These data evidence a greater efficiency for BMPC than BMAC.